2011
DOI: 10.1074/jbc.m111.235184
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Down-regulation of Overexpressed p185 Protein of Transformed Cells by the Antibody chA21

Abstract: p185her2/neu belongs to the ErbB receptor tyrosine kinase family, which has been associated with human breast, ovarian, and lung cancers. Targeted therapies employing ectodomain-specific p185 her2/neu monoclonal antibodies (mAbs) have demonstrated clinical efficacy for breast cancer. Our previous studies have shown that p185 her2/neu mAbs are able to disable the kinase activity of homomeric and heteromeric kinase complexes and induce the conversion of the malignant to normal phenotype. We previously developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Competitions on HER2/ECD binding for the S90 scFvs against 4 positive control antibodies (Fig. 6a), where the x-ray structures of the antibody-HER/ECD complexes are known (A2144, Fab3745, pertuzumab1, and trastuzumab2; see Fig. 6b), indicated that the prevalent M32-M62 epitope group was situated on the domain I of HER2/ECD and was near to – but not overlapped with – the epitope of A21, as demonstrated in the epitope mapping with HDX-MS (site E1 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Competitions on HER2/ECD binding for the S90 scFvs against 4 positive control antibodies (Fig. 6a), where the x-ray structures of the antibody-HER/ECD complexes are known (A2144, Fab3745, pertuzumab1, and trastuzumab2; see Fig. 6b), indicated that the prevalent M32-M62 epitope group was situated on the domain I of HER2/ECD and was near to – but not overlapped with – the epitope of A21, as demonstrated in the epitope mapping with HDX-MS (site E1 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since HER2 has no specific ligand, its antibodies usually inhibit tumor cells by blocking dimerization and activation of the receptor and mediating killing effect of immune system. 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, nine amino acids (G, P, S, N, H, D, E, V, and L) were over-represented in more than 20 positions, which showed high overlap with the amino acids that were selected in previous studies for antibody affinity evolution (Gonzalez-Munoz et al, 2012). According to the chA21-ErbB2 complex crystal structure, the majority of CDR mutations are located within the central or peripheral regions of antibody-antigen binding interface (Zhou et al, 2011). However, a few CDR mutations are quite far away from the binding interface and can in no way make direct contacts with the antigen.…”
Section: Discussionmentioning
confidence: 97%